Comparative Analysis of Classification Algorithms Using CNN Transferable Features: A Case Study Using Burn Datasets from Black Africans - Aliyu Abubakar (Applied System Innovation, 2020)
Burn is a devastating injury affecting over eleven million people worldwide and more than 265,000 affected individuals lost their lives every year. Low- and middle-income countries (LMICs) have surging cases of more than 90% of the total global incidences due to poor socioeconomic conditions, lack of preventive measures, reliance on subjective and inaccurate assessment techniques and lack of access to nearby hospitals. These factors necessitate the need for a better objective and cost-effective assessment technique that can be easily deployed in remote areas and hospitals where expertise and reliable burn evaluation is lacking. Therefore, this study proposes the use of Convolutional Neural Network (CNN) features along with different classification algorithms to discriminate between burnt and healthy skin using dataset from Black-African patients. A pretrained CNN model (VGG16) is used to extract abstract discriminatory image features and this approach was due to limited burn images which made it infeasible to train a CNN model from scratch. Subsequently, decision tree, support vector machines (SVM), naïve Bayes, logistic regression, and k-nearest neighbour (KNN) are used to classify whether a given image is burnt or healthy based on the VGG16 features. The performances of these classification algorithms were extensively analysed using the VGG16 features from different layers.